2018
DOI: 10.1007/8904_2018_125
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hepatic Porphyrias in Colombia: An Analysis of 101 Patients

Abstract: Diagnosis and treatment of AHPs in Colombia have improved in recent decades. However, there are still important shortcomings to address.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Acute rhabdomyolysis has been described several times associated with acute neurovisceral crisis in AHP, most commonly in the context of severe presentations in the ICU with hydroelectrolytic disturbances and preceded by autonomic neuropathy and acute encephalopathy ( Devars du Mayne et al, 1987 ; Marsden and Peters, 2004 ; García-Martul et al, 2008 ; Yrjönen et al, 2008 ; Jaramillo-Calle and Acevedo, 2019 ). Isolated or recurrent episodes of rhabdomyolysis are not typically observed in AHP ( Adams and Amaya, 2014 ), and it is not usual to represent the presenting clinical event, and myoglobinuria is a variable finding ( Yrjönen et al, 2008 ; Adams and Amaya, 2014 ; Karakulova et al, 2019 ).…”
Section: The Neuromuscular Manifestations Of Acute Hepatic Porphyria and Their Pathophysiological Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute rhabdomyolysis has been described several times associated with acute neurovisceral crisis in AHP, most commonly in the context of severe presentations in the ICU with hydroelectrolytic disturbances and preceded by autonomic neuropathy and acute encephalopathy ( Devars du Mayne et al, 1987 ; Marsden and Peters, 2004 ; García-Martul et al, 2008 ; Yrjönen et al, 2008 ; Jaramillo-Calle and Acevedo, 2019 ). Isolated or recurrent episodes of rhabdomyolysis are not typically observed in AHP ( Adams and Amaya, 2014 ), and it is not usual to represent the presenting clinical event, and myoglobinuria is a variable finding ( Yrjönen et al, 2008 ; Adams and Amaya, 2014 ; Karakulova et al, 2019 ).…”
Section: The Neuromuscular Manifestations Of Acute Hepatic Porphyria and Their Pathophysiological Mechanismsmentioning
confidence: 99%
“…A summary of the main pathogenic and likely pathogenic variants reported to date in the four genes associated with AHP is provided ( Figure 4 ). Most pathogenic variants related to AHP are classified as missense, small deletions, and small insertions or duplications ( Chen et al, 2016 ; O’Malley et al, 2018 ; Jaramillo-Calle and Acevedo, 2019 ). AIP, VP, and most cases of HCP are associated with autosomal dominant pattern of inheritance and occurs due to heterozygous pathogenic variants, respectively, in HMBS , PPOX , and CPOX genes.…”
Section: Genetic Basis Of Acute Hepatic Porphyriamentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there is a lack of epidemiological data on AIP worldwide, but Europe performed large scale prospective study to investigate the incidence of porphyrias ( Elder et al, 2013 ). And multiple countries such as South Africa ( Fortgens et al, 2017 ), the United States ( Bonkovsky et al, 2014 ), Argentina ( Cerbino et al, 2015 ), Colombia ( Jaramillo-Calle and Aguirre Acevedo, 2019 ), and Russia ( Goncharova et al, 2019 ) have reported cohort studies on AIP. And with the development of sequencing technology, more and more AIP patients have been reported in China.…”
Section: Introductionmentioning
confidence: 99%